PENERAPAN APLIKASI PERJALANAN DINAS DI KANTOR SEKRETARIAT DAERAH (SETDA) KOTA SERANG - R. Hudan Muchtadi; Noppy Hadisuwarno; Sigit Auliana (Universitas Majalengka, 2024)
This study aims to design and develop a business trip application at the Regional Secretariat of Serang City to facilitate the management of official travel processes. The application is designed to support the digitalization of administrative procedures, from travel requests, budget management, to trip reporting. The system development uses the Agile methodology, enabling rapid iteration based on user feedback. This web-based system is built using PHP programming language and MySQL database. The application is expected to improve efficiency, accuracy, and transparency in official travel management and minimize potential manual errors.